Treatment of Aberrant Frenulum, Frenectomy and Frenotomy (Revista Nacional de Odontología, 2017)
Introduction: Mucogingival deformities have an impact on the function and aesthetics of patients, beingof congenital, developmental or acquired origin. A mucogingival condition is a deviation from the normal anatomy of the tissues located between the gingival margin and the mucogingival junction. Theseconditions include alterations of the insertion of frenula and the depth of the vestibule. Aberrant frenulaof lips inside the cavity do not usually cause pathologies to be considered; however, in some cases,its overinsertion may cause periodontal, functional, aesthetic and phonetic deformities. The removal offrenula may be through either full exeresis (frenectomy) or lateral or apical replacement (frenotomy).Each procedure has its indications/contraindications, advantages and disadvantages. Aim: The present review summarizes the main sources of information in the Scopus, Pubmed, Scieloand lilacs databases related to the surgical treatment of aberrant frenula. Conclusion: Both procedures are effective in the disinsertion of frenulum fibers; frenectomy can causeslight formation of bridle scars, while frenotomy has a lower incidence thereof. An alternative option toconventional techniques is the use of laser to remove the frenulum.
Keywords: plastic surgery; frenulum of lips; frenulum of tongue; gingival recession